The Referring to Regional Dress: Dutch Traditional Costumes as Recurring Inspiration for Contemporary Fashion Design - Kargól, Marta (Załącznik Kulturoznawczy, 2019)
In this article, the author aims to classify and analyze the use of Dutch regional costumes as a source of inspiration by contemporary fashion designers. The strategies have been assigned the following concepts taken from literary (and cultural) studies: quote, allusion, paraphrase, pastiche and translation. The definitions of these concepts are used as tools for interpreting the ways in which Dutch regional costumes are made present by fashion designers in their outfits. The article discusses the role of distance and similarities between the source of inspiration and its interpretation in the contemporary fashion design.